The Influence of Hijab Celebrity Instagram as an Endorsement on Purchase Intention - Devi Noviyanti; Restu Khaliq (Alhadharah: Jurnal Ilmu Dakwah, 2021)
Celebrity endorsers influence celebrity endorsers who wear the hijab on a person's purchase intentions. A total of 91 respondents were taken in this study, all of whom had seen celebrity endorsers wearing hijabs advertising products/services on Instagram social media. SmartPLS software version 2.0.M3 was using, and research shows a significant influence of trustworthiness, attractiveness, and expertise on one's purchasing intentions. The T-statistic value of all dimensions of the celebrity endorser variable towards purchase intentions is more significant than 1.96, by 3.213, 3.121, and 2.832, respectively.Keywords: celebrity endorsers, hijab, purchase intentions.